“Who are the ladies?” : women’s representation and identity construction in the HBO series ‘Girls’ - Mustonen, Tiina (2015)
This research paper examines the representations and identities constructed in the HBO television series 'Girls', which is considered one of the most groundbreaking television series of recent years due to its realistic and diverse female characters. In this paper, I analyse relevant examples from the first season of the series. The analysis is based on Critical Discourse Studies and various theories of gender and language. The main focus is not only on the linguistic construction of representations and identities, but also on multimodality. In addition to analysing how these linguistic and multimodal features affect representation, it is also considered how the series challenges today's norms of women in media.